Landscape of Global Pediatric Oncology Publications: A Cross-Sectional Analysis - María Fernanda García Garza; Oscar Gutiérrez Treviño; Saman K. Hashmi; Carlos Rodríguez-Galindo; Daniel C. Moreira (JCO Global Oncology)
PURPOSEThe academic field of global pediatric oncology is expanding as cancer becomes increasingly recognized as a global health priority for children and adolescents. Here, we aimed to explore the representation of authors, the geographic distribution of research, and the research approaches being used in global pediatric oncology.METHODSArticles published in JCO Global Oncology (JCO GO) and Pediatric Blood and Cancer on the topic of global pediatric oncology were analyzed. For each article, data were collected on the study design, the research location, and the authorship demographics. Descriptive frequencies were reported for all items.RESULTSOverall, 296 studies met the inclusion criteria to be considered relevant for global pediatric oncology. Of these, 259 (87.5%) were research articles. Of the research articles, 228 (88.0%) were observational and 117 (51.3%) were retrospective cohort analyses. Thirty-eight studies (12.8%) had a global focus or were unrelated to a geographic context, 54 (18.2%) were regional, and 204 (68.9%) were specific to a single country. Females represented 163 (55.8%) of first authors, 138 (46.6%) of senior authors, and 159 (53.7%) of corresponding authors. Furthermore, 121 (41.4%) first authors, 163 (55.1%) last authors, and 142 (48.0%) senior authors were from high-income countries (HICs). The United States (n = 81) and India (n = 40) had the most corresponding authors. Thirty-six (17.6%) articles had research conducted in low- and middle-income countries (LMICs), and the first, senior, and corresponding authors were from HICs.CONCLUSIONOur analysis shows that researchers from LMICs are under-represented as authors of global pediatric oncology publications. Further studies are needed to evaluate the factors that contribute to inequalities in global pediatric oncology research.